Comparative analysis of different filling materials in deciduous teeth - Barnwai, Hafsah O.; Alkhowaiter, Sawssan S.; Alduhiman, Salma H.; Almarri, Felwah A.; Alforehi, Saja S.; Alotaibi, Lana G.; Alshehri, Rayan A.; Althebaiti, Saja; Alyahya, Faisal M.; Baeti, Bassmah A.; Al-Resayes, Soundous S. (International Journal Of Community Medicine And Public Health, 2024)
Dental caries in pediatric patients presents a significant challenge in maintaining oral health, making the choice of filling materials for deciduous teeth crucial for long-term success. Various restorative materials, including composite resins, glass ionomer cements (GICs), and resin-modified glass ionomers (RMGICs), have been used, each with distinct properties regarding durability, biocompatibility, and aesthetic outcomes. Composite resins are well-regarded for their ability to closely match the natural color of teeth, making them ideal for anterior restorations. However, they are technique-sensitive and may not provide sufficient durability in posterior regions subjected to high stress. Glass ionomer cements, known for their ease of placement and fluoride release, offer functional benefits in high-caries-risk patients, despite their lower aesthetic quality and susceptibility to wear over time. Resin-modified glass ionomers attempt to combine the strengths of both composites and GICs by improving durability and aesthetics while maintaining the fluoride-releasing property. The safety and biocompatibility of these materials also play a pivotal role in pediatric dentistry. While composite resins may release small amounts of bisphenol A (BPA), which has raised concerns about its potential health risks, GICs and RMGICs are generally considered safer due to their simpler chemical composition and fluoride release. In terms of functional longevity, composite resins offer better wear resistance compared to GICs, though resin-modified glass ionomers provide a compromise with improved strength and ease of use. Ultimately, the choice of restorative material should consider the specific clinical circumstances, including the child’s caries risk, tooth location, and the balance between aesthetic and functional needs. No single material is universally ideal for all cases, and a tailored approach is necessary to optimize outcomes in pediatric dental restorations.